A clinical study of the cutaneous manifestations of hypothyroidism in kashmir valley - Mohammad Abid Keen; Iffat Hassan; Mohammad Hayat Bhat (Wolters Kluwer Medknow Publications, 2013)
Background: Thyroid disorders are known to involve all the organ systems of the body, the skin being no exception. The association of thyroid disorders with cutaneous manifestations is complex. Both hypothyroidism and hyperthyroidism are known to cause these changes. Aims: The present study was designed to ascertain the varied cutaneous manifestations of hypothyroidism. Materials and Methods: This study was a hospital based clinical study conducted in collaboration with the Endocrinology Division (Department of Medicine) of SMHS Hospital (associated teaching hospital of Government Medical College Srinagar), over a period of one year, from May 2010 to May 2011. Four hundred and sixty consecutive diagnosed cases of hypothyroidism constituted the subject material for the study and were evaluated for the presence of any cutaneous manifestation. Results: In our study group of 460 patients, there were 416 females and 44 male patients. The predominant cutaneous symptom in our hypothyroid patients was dry coarse skin (65.22%), followed by hair loss (42.6%) and puffy edema (38.48%). The most common cutaneous sign observed in hypothyroid patients was xerosis (57.17%), followed by diffuse hair loss (46.09%), altered skin texture (31.74%), coarse scalp hair (29.35%) and puffy face (28.69%). Conclusions: The interaction between thyroid gland and skin is of profound clinical importance in dermatological practice. So, dermatologists need to be cognizant of the ways in which these two organs interact.